CORRELATION KNOWLEDGE WITH PSYCHOLOGY RESPONSE OF TEENAGE GIRLS IN CONFRONT MENARCHE - Nisak Luvi Mega Irawati; Budiono Budiono; Bagus Setyoboedi (Universitas Airlangga, 2021)
Abstract Background: Adolescence is a transition from children to adulthood. In adolescence menarche will occur, menarche is the first menstruation in young women which occurs between 1.5 to 3 years after thelarche. The average menarche occurs at the age of 12 and 13 years. When Menarche happens, many changes occur, one of which is psychological change. Changes in the level of knowledge of adolescents about the level of knowledge of adolescents about menarche. Knowledge about menarche can be obtained through families, print media, electronics, or health workers (midwives, doctors, nurses). Examining the relationship of knowledge level with prepubertal adolescent girls psychological responses in menarche conversation. Method: This study was an observational analytic study with a cross sectional study design. The number of samples was 41 students with total sampling techniques. To find out the relationship between variables, the data test with the chi-square test. Results: The results showed that most teenagers' knowledge in the knowledge category was 70.73%. While the psychological response is mostly in the negative category (68.3%). Contingency coefficient results showed a p value of 0.270 (p <0.05). Conclusion: These data indicate that there is no correlation between knowledge and psychological responses of pre-puberty teenage girls in the face menarche.